Impact of TNF-α Gene Polymorphisms on Pancreatic and Non-Small Cell Lung Cancer-Induced Cachexia in Adult Egyptian Patients: A Focus on Pathogenic Trajectories - Yehia, Rana; Schaalan, Mona; Abdallah, Dalaal M.; Saad, Amr S.; Sarhan, Neven; Saleh, Samira (Frontiers in Oncology, 2021)
Background: Cachexia is a frequent syndrome in pancreatic and non-small cell lung (NSCL) cancer patients. The storm of cancer-induced inflammatory cytokines, in particular TNF-α, is a crucial pathogenic mechanism. Among the molecular alterations accused of cancer-induced cachexia, TNF-α 308 G/A (rs1800629) and −1031T/C (rs1799964) are single-nucleotide polymorphisms (SNPs) within the gene encoding this pro-inflammatory cytokine. Recent studies have demonstrated the crucial role of noncoding micro RNAs (miRNAs) in pathogenesis of different diseases including cachexia. Moreover, the mechanistic cytokine signaling pathway of miR-155, as a TNF-α regulator, supports the involvement of SOCS1, TAB2 and FOXP3, which are direct targets of TNF-α gene. Aim: A case-control study (NCT04131478) was conducted primarily to determine the incidence of TNF-α 308 G/A (rs1800629) and −1031T/C (rs1799964) gene polymorphism in adult Egyptian patients with local/advanced or metastatic pancreatic or NSCL cancer and investigate both as cachexia risk factors. The association of gene polymorphism with cachexia severity and the expression of miR-155 in cachectic patients were analyzed. A mechanistic investigation of the cytokine signaling pathway, involving SOCS1, TAB2 and FOXP3, was also performed. Results: In both pancreatic and NSCL cancer cohorts, the mutant TNF-α variant of 308 G/A was positively associated with cachexia, on the contrary that of 1031T/C was negatively associated with cachexia in NSCL cancer patients. miR-155 was higher in cachexia and in alignment with its severity in cachectic group as compared to non-cachectic group in both pancreatic and NSCL cancer patients. Though TAB2 did not change to any significant extent in cachectic patients, the levels of SOCS1 and FOXP3 were significantly lower in cachectic group as compared to non- cachectic group. Conclusion: Carriers of the A allele 308 G/A gene and high miR-155 are at greater risk of cachexia in both pancreatic and NSCL cancer patients; however, the mutant variant of 1031T/C gene is protective against cachexia in NSCL cancer patients. Finally, high levels of miR-155 in the cachectic group lead to negative feedback inhibition of both SOCS1 and FOXP3 in both the pancreatic and NSCL cancer patients.